‘Summer Pink’ – A New Pink, Fancy-Leaved Caladium Variety - Zhanao Deng (EDIS)
‘Summer Pink’ is a new fancy-leaved caladium variety developed by the University of Florida’s Institute of Food and Agricultural Sciences (UF/IFAS) caladium breeding program for use in large containers and shady locations in the landscape (Deng and Harbaugh 2012). Leaves of this variety have a pink face and pink veins. In replicated field and greenhouse trials, ‘Summer Pink’ performed comparably or better than ‘Fannie Munson’ and ‘White Queen’, two pink caladium varieties commonly used in containers and landscapes. This 4-page fact sheet was written by Zhanao Deng, and published by the UF Department of Environmental Horticulture, August 2012.